(untitled) (INNOVATIVE ECONOMY, 2025)
Herman L.T., Uniiat A.V. ECONOMIC EFFECTS OF TRADE AND MIGRATION IN THE CONTEXT OF INTERNATIONAL STRATIFICATION Purpose. The aim of the article is to analysis of the economic effects of the interaction between international trade and migration processes in the context of global stratification, identification of systemic factors causing uneven distribution of profits between countries with different levels of development, and formation of current trends in the global economy. Methodology of research. The following research methods were used to achieve the set goal: analysis and synthesis to establish links between migration processes, trade and country stratification; induction and deduction to draw conclusions based on the analysis; the graph analytical method was used to visualise dynamics and structure; econometric modelling was used to assess the impact of key trade and migration indicators on the inequality of countries’ development. Findings. Foreign trade flows and the impact of trade on the stratification of countries in the global economy were analysed in the article. The impact of labour migration on national economies is analysed and new challenges caused by migration processes are outlined. A relationship between global integration indices, migration attractiveness and income inequality has been established. It has been found that the institutional capacity of states plays an important role in reducing stratification factors through trade and migration. Countries that are forming new centres of economic power through their flexible migration policies and export-oriented strategies are considered. Originality consists of a detailed analysis of the impact of migration processes and trade on the uneven development of countries in the global economy. A graphical model of the impact of trade and migration on the economic development of countries with different income levels is substantiated. Practical value. The proposed results of the study of the economic effects of trade and migration on international stratification can be used in the development of policies, programmes and strategies at both the national and international levels. Key words: migration, international migration processes, labour migration, international trade, global economy, global stratification, inequality.